Analytical model for assessing fatigue limit of welded joints of ferritic-pearlitic steels - K. A. Molokov; V. V. Novikov; A. P. German (Advanced Engineering Research, 2020)
Introduction. Microdefects and zones with stress concentration in welded joints cause fatigue macrocracks. Such damage is potentially dangerous, especially if the fatigue life of the structure is almost exhausted. In this case, the crack size is close to the critical value, and it is crucial to determine its length. The paper considers the development of an engineering analytical model for assessing the critical crack length and endurance limit of welded joints with the formed grain in the structure of ferrite-pearlitic steels after welding. Materials and Methods. The theory and methods of fracture mechanics at the mesoscale are used. A simple analytical dependence is obtained, which provides determining the critical dimensions of a macrocrack for ferrite-pearlite steels without using the Griffiths formula. . The calculation results of the critical crack lengths of various steels depending on their yield strength are presented. An analytical dependence of the endurance limit calculation for the most dangerous symmetric loading cycle, according to the standard set of mechanical characteristics and the average grain diameter of ferrite-pearlite steel, is presented. Results. Structural deformation analysis of the crack propagation process has been performed. On its basis, an engineering technique for assessing the endurance limit is developed. A mathematical model that enables to calculate the endurance limit and the critical crack length in the components of welded assemblies of large-sized facilities, considering periodic loads of a symmetrical cycle, is developed. Using this model, it is possible to estimate the degree of metal sensitivity to the original characteristics (yield stress, Poisson's ratio, grain diameter, relative constriction, Young's modulus, power-law hardening coefficient, etc.).Discussion and Conclusion. Under stresses corresponding to the steel endurance limit, the critical crack opening rates of the tip and edges approach each other. Energetically, this moment approximately corresponds to the transition of the crack to an unstable state. The accumulation of one-sided plastic deformations causes the limiting state of plasticity of the region adjacent to the crack tip and its avalanche-like or sharply accelerated motion. This critical area is interrelated with the grain diameter of the material, the characteristic of critical plasticity and the critical opening at the crack tip at the fatigue limit. The proposed analytical dependences can be used to assess the residual life and the fatigue limit of welded structures, the influence of various factors on the fatigue limit of welded joints of ferrite-pearlitic steels used in mechanical engineering, shipbuilding, pipeline transport, etc